Perfectionist self-presentation and altruistic attitudes during adulthood - Elena A. Truhan; Olga N. Savchuk (Saratov State University, 2022)
The problem of effective tactics of personal self-presentation in various situations of social interaction is becoming increasingly important. The phenomenon of perfectionism as a person's desire for perfection, exceptional achievements and admiration from others, is becoming increasingly common both in professional and personal spheres. Objective: to identify the relationship between perfectionist self-presentation and altruistic attitudes in different periods of adulthood. It is hypothesized that there is gender and age characteristics and the interrelationships of perfectionist self-presentation and altruistic attitudes during adulthood. The study sample consisted of 90 respondents (men and women) aged 20 to 75 years (Minsk). Three periods of adulthood were compared: early (20-40 years), middle (40-60 years) and late (over 60 years). To diagnose perfectionist self-presentation, the Russian-language version of P. Hewitt's Perfectionist Self-Presentation Scale was used (adaptation by A. A. Zolotareva); to determine the manifestation of altruistic attitudes, the methodology for diagnosing socio-psychological attitudes of the individual (O. F. Potemkin) was used. The authors obtained the data on gender and age characteristics and interrelations of perfectionist self-presentation and altruistic attitudes during adulthood. Through altruistic actions, men strive to create an image of a perfect person, demonstrate socially desirable behavior (altruism as a secondary benefit and a tool for self-promotion). With age, the level of perfectionist self-presentation decreases, and the manifestation of altruistic attitudes increases, reaching its peak in late adulthood. Empirically, the authors proved the existence of a relationship between perfectionist self-presentation and altruistic attitudes during late adulthood (the willingness to act for the benefit of others, to patronize people who suffer or experience difficulties, is associated with the desire to receive admiration and approval from others). Interpersonal interaction is shown to be regulated by empathy as well as by image and reputation goals, and altruism is one of the tactics of impression management. Taking care of one's reputation, public opinion, and image are important reasons for benevolence and prosocial behavior.